2009
DOI: 10.1007/s00795-009-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of micro-RNAs in human esophageal squamous cell carcinoma using RT-PCR

Abstract: To develop novel therapeutic and diagnostic methods for esophageal cancer, it is important to understand the precise biological mechanism. Micro-RNAs (miRNAs) seem to be crucial factors in diverse regulation pathways. In this study, we analyzed the expression of mature miRNAs in esophageal squamous cell carcinoma (ESCC). The expression of 73 miRNAs was quantified by qRT-PCR in 30 primary ESCC specimens. We examined the correlation between miRNA expressions and the clinicopathological factors and prognosis of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
3
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 24 publications
3
73
3
2
Order By: Relevance
“…Compared with NEST, a significant down-regulation of miR-210 expression was noted in ESCC. On the other hand, the expression of miR-31, which has been reported to be not altered between ESCC and NEST (16,17), showed no significant difference (Fig. 1B).…”
Section: Mir-210 Expression Is Significantly Down-regulated In Escc mentioning
confidence: 77%
“…Compared with NEST, a significant down-regulation of miR-210 expression was noted in ESCC. On the other hand, the expression of miR-31, which has been reported to be not altered between ESCC and NEST (16,17), showed no significant difference (Fig. 1B).…”
Section: Mir-210 Expression Is Significantly Down-regulated In Escc mentioning
confidence: 77%
“…miR-132 expression has been reported to be increased in several types of cancers including lung cancer (14), squamous cell carcinoma of the tongue (23), colorectal carcinoma (24) and esophageal cancer (25). However, decreased miR-132 expression has been observed in osteosarcoma (26) and liver cancer (27).…”
Section: Discussionmentioning
confidence: 99%
“…The global miRNA expression analyses (hierarchical clustering and principal component analysis) showed that the expression profiles of the miRNAs differed between the cisplatin-sensitive and -resistant cell lines (Figure 2), and expression levels of 45 miRNAs were changed by more than fourfold in cisplatin-sensitive cell lines as compared with cisplatin-resistant cell lines (Supplementary Table 1). Subsequently, the expression levels of the 10 miRNAs that were selected according to the miRNA microarray data and literature search [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were validated by quantitative reverse transcription-PCR. This confirmed that miR-141, miR-21, miR-19b, miR-200a, miR-19a, miR-27a, miR-20a and miR-20b were expressed at significantly higher levels in the cisplatinresistant lines, and miR-205 and miR-224 at significantly lower levels than in the cisplatin-sensitive cell lines (Po0.05) (Table 1).…”
Section: Cisplatin-sensitive and -Resistant Human Escc Cell Linesmentioning
confidence: 99%